Social Media Insights for Non-luxury Fashion SMEs in Emerging Markets: Evidence from Young Consumers - Senanu, Bright; Anning-Dorson, Thomas; Tackie, Nii Nookwei (Journal of Fashion Marketing and Management (Emerald Publishing Limited), 2023)
Purpose The study investigates the factors that influence young consumers (Gen Zs and Ys) in emerging markets to engage fashion ads of non-luxury fashion retail small- to medium-size enterprises (SMEs) on social media. Through a desk assessment of practice and the phenomenon's available evidence in the extant literature, four main drivers were delineated, reviewed and subsequently tested to influence young consumers' behavioural engagements of emerging markets' fashion SMEs' social media contents. Design/methodology/approach A non-probability sample of 1,150 respondents (Gen Y and Z combined) in Ghana, an emerging market, formed the sample for the study. The respondents assessed four empirically identified antecedents (sales campaigns, relevant sales-related information, catchy and inspiring product/brand photo/video and consumer-generated contents) that are likely to influence their behavioural engagement on social media platforms (Instagram, Facebook, WhatsApp and Twitter). SmartPLS (version 3.3.3) was employed to perform partial least square structural equation modelling. Findings The results showed that to engage fashion-related ads, particularly from non-luxury fashion SMEs, young consumers consider sales campaigns, cues from consumer-generated contents, as well as quality and inspiring videos and photos. Less attention is given to relevant sales-related information. Practical implications The three significant drivers of engagement found in the current study provide managerial knowledge for non-luxury fashion SMEs in emerging markets. Videos and still pictures must be of high definition and quality. Short and long promotional campaigns may drive positive behavioural engagements. Interactivity between fashion SMEs and young consumers is encouraged as it precipitates the positive engagement behaviours enabled by social media. The study concludes with actionable recommendations for the non-luxury fashion SME sector in emerging economies. Originality/value The study is the first of its kind to ascertain what drives young consumers' engagement with non-luxury fashion SMEs on social media. It provides managerial insights and guidance to SMEs in emerging markets on effective social media fashion retailing targeted mainly at digital natives, the dominant generational cohorts on social media in most emerging economies.
Research Article
Keywords: Young consumers; Social media insights; SMEs; Non-luxury fashion marketing; Emerging markets; Customer behavioural engagement